Trends and Determinants of Using Delivery Assistance by Health Workers: A Secondary Analysis Using the 2007–2017 Indonesian Health and Demographics Survey - Idris, Haerawati; Syafriyanti, Willyana (UI Scholars Hub, 2022)
Background: The World Health Organization reports that approximately 295,000 women died during or after their pregnancy and delivery in 2017. However, such deaths can be prevented by using delivery assistance from health workers. This study aims to analyze the trends and determinants of using delivery assistance by health workers in Indonesia. Methods: A quantitative cross-sectional design is adopted to analyze secondary data from the Indonesian Health Demographic Surveys in 2007, 2012, and 2017. The sample includes married women that are selected according to inclusion and exclusion criteria: 15.011 respondents in 2007, 14.989 in 2012, and 15.179 in 2017. Data are analyzed using logistic regression statistical tests. Results: This study shows the significant increase of using delivery assistance by health workers in Indonesia, from 53.8% in 2007, 68.8% in 2012, to 77.9% in 2017. Age, residence in the Java/Bali region, residence in urban areas, high and secondary education, high economic status, complete antenatal care visits, and knowing the signs of danger during pregnancy have significant relationships with delivery assistance by health workers among women. After being controlled by another factor, higher education is the most dominant factor associated with using delivery assistance by health workers among women in Indonesia (p < 0.001; Prevalence Ratio (PR) of 3.727 (3.123–4.447). Conclusions: Women’s education is the most important factor in delivery assistance by health workers utilization. Increasing knowledge regarding utilization of health worker assistance during delivery can be carried out through educational information, counseling or seminars, the Internet, and other media that are expected to increase information and awareness to take advantage of such service.